2007
DOI: 10.1016/j.bmcl.2007.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein farnesyltransferase substrate specificity using synthetic peptide libraries

Abstract: Farnesylation, catalyzed by protein farnesyltransferase (FTase), is an important posttranslational modification guiding cellular localization. Recently predictive models for identifying FTase substrates have been reported. Here we evaluate these models through screening of dansylatedGCaaS peptides, which also provides new insights into the protein substrate selectivity of FTase.Farnesylation is a posttranslation modification that tags proteins with a farnesyl (C 15 ) isoprenoid supplied by farnesyl diphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…For all of these peptide panels, the reactivity of FTase with the peptides decreases with increasing polarity of the a 2 residue for the polar amino acids as defined in Figure 2a; in fact, the reactivity of FTase with some of the peptides with charged a 2 residues is below the detection limit of the fluorescence assay (Table 1). This trend indicates that the preference for hydrophobic residues at the a 2 position is general, as previously proposed (1, 3, 14, 17, 25, 44, 45). In contrast, for the “nonpolar” amino acids, the dependence of reactivity on the volume of the a 2 residue is dependent on the identity of the X group (Figure 3); proline-containing substrates (open triangles) are excluded from the correlation analysis as they appear to be outlier points, possibly due to changes in conformation of the peptide substrate.…”
Section: Resultssupporting
confidence: 84%
“…For all of these peptide panels, the reactivity of FTase with the peptides decreases with increasing polarity of the a 2 residue for the polar amino acids as defined in Figure 2a; in fact, the reactivity of FTase with some of the peptides with charged a 2 residues is below the detection limit of the fluorescence assay (Table 1). This trend indicates that the preference for hydrophobic residues at the a 2 position is general, as previously proposed (1, 3, 14, 17, 25, 44, 45). In contrast, for the “nonpolar” amino acids, the dependence of reactivity on the volume of the a 2 residue is dependent on the identity of the X group (Figure 3); proline-containing substrates (open triangles) are excluded from the correlation analysis as they appear to be outlier points, possibly due to changes in conformation of the peptide substrate.…”
Section: Resultssupporting
confidence: 84%
“…In both cases, the isoprenoid is attached to the cysteine in a C-terminal “Ca 1 a 2 X” sequence. While the “a” residues guide substrate ability,3, 4 the X position is the most important selectivity factor for FTase versus GGTase-I. Those peptides bearing X residues of Ser, Gln, and Met are farnesylated (Ras proteins and others) and those bearing Leu are geranylgeranylated (Rho proteins and others).…”
mentioning
confidence: 99%
“…It is not known if the alternate farnesylation of any geranylgeranylated proteins would confer resistance to GGTIs, and this is a key question with regard to their evaluation 10. As a complement to proteomic methods,13, 14 we have employed peptide libraries to evaluate FTase substrate specificity 3. In this study, we screened 41 dansyl-GCaaL (DnGCaaL) peptides versus FTase, and found a surprising number of efficient substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prenylation is required for the proper function of many proteins, including members of the Ras and Rho superfamilies of small GTPases (2,6). FTase is known to modify a large number of proteins within the cell (7)(8)(9)(10); recent experimental and theoretical/computational studies using small peptide substrates suggest that several hundred proteins within the human proteome may be farnesylated (11)(12)(13)(14). Based on peptide reactivity and structural studies of FTase-substrate complexes, a minimal substrate recognition motif for FTase is a peptide or protein containing a cysteine four amino acids from the C terminus (-CXXX).…”
mentioning
confidence: 99%